Iptek Bagi Masyarakat (Ibm) Tusuk Sate Ponorogo 2016 - Purwanto .; Pinaryo .; Fadelan . (Universitas Muhammadiyah Ponorogo, 2017)
Sate is a typical food of Ponorogo which its existence tends to increase from year to year in line with the increasing of population and welfare. The existence of sate has multiplier economy effect particularly in society and region in general. Sate sellers are almost spread in all over subdistrict both of within and outside the city. Relatedted to the availability of skewer which is still made traditionally with the result under capacity and not hygienic. Thus the main problem is how to produce skewer in sufficient quantities with good quality and hygienic. Ipteks Bagi Masyarakat (IbM) of skewer from Economic Faculty Muhammadiyah University of Ponorogo attempts to solve the problem with production pattern approach from conventional into mechanical. Mechanical production is expected capable to provide skewer in sufficient quantities, qualified and hygienic skewer. Moreover, in society aspect it is expected to increase prosperity of skewer producer and sate seller by provide workfield.